Choice of Frequency and Vehicle Size in Rail Transport: Implications for Marginal External Costs - Piet Rietveld; Jasper Dekkers; Stefan van Woudenberg (Tinbergen Institute, 2001)
Frequency of services and vehicle size are important policyinstruments of railway companies. Extending Mohring's basic'square root model' for frequencies, we arrive at more generalformulations for frequency, vehicle size and price underalternative regimes of welfare and profit optimisation. It appearsthat in the more refined models the frequency responseof railway companies with respect to changes in passenger volumes isnot far removed from the standard square rootresult. After the formulation of theoretical models we also carry outan empirical analysis where choice of frequency andvehicle size are analysed with special attention paid to the level ofoccupancy rates. It appears that average occupancyrates are low in rail transport. As a result the frequency andvehicle size response of the railway company appears to below. It is estimated that an increase in the number of passengers of1% leads to an increase in the supply of capacity ofabout 0.5 % (a frequency increase of about 0.35% and an increase ofvehicle size of about 0.15% ). This has importantimplications for the environmental costs of railway firms. Given thelow occupancy rate, an additional passenger does notlead to a proportional increase in capacity so that the marginalcosts are lower than the average costs.
Keywords: 330; Eisenbahnpersonenverkehr; Nachfrage; Externer Effekt; Verkehrsökonomik; Theorie